Systemy społeczne w organizacjach: Social systems in organizations - Szaniawska, Anna (Management and Administration Journal, 2021)
This article presents the definitions, characteristics and types of groups and teams. It also presents the benefits of the functioning of these community in organizations and presents the comparison of them. The article also discusses the coherence of groups and teams, and factors affecting it.